Diagnostic Tests for SARS COV-2: Application, Challenges and Recommendations - Salih, Mohibullah; Waqar, Delaqa; Nijrabi, Hasibullah Baha; Saiqal, Oniba (Eximia, 2023)
Background: The recent pandemic of human coronavirus infections, at the beginning of the 21st century, have shown the prominent roles of rapid and accurate diagnostic technologies to contain the emerging and re-emerging infections. To control such a large-scale crisis, early identification and prevention of infection are essential. Prompt identification of cases relies on the accurate diagnostic technologies. Before analysis, appropriate sample collection is essential for making a precise molecular diagnosis of SARS-COV-2 (Severe Acute Respiratory Syndrome Coronavirus-2). To prevent further spread of infection and obtain consistent results, proper preventive measures must be taken into consideration to keep laboratory staff safe. Despite the development of specific and sensitive point-of-care tests and serological immunoassays which are considered supplementary methods for diagnosing SARS-COV-2, RT-PCR (Reverse-Transcriptase Polymerase-Chain-Reaction) remains the gold standard performed on respiratory specimens. Upon completion of the sample analysis, testing results must be interpreted using both molecular and serological findings. Finally, random-access, integrated devices available for the purpose of care with scalable capacities will facilitate the rapid and accurate diagnosis and monitoring of Severe Acute Respiratory Syndrome Corona Virus-2 (SARS CoV-2) infections. Objectives: This review covers the types of sample collection, current diagnostic techniques for COVID-19 and challenges in their application Methods: A literature search was performed on the lines for a narrative review, but including features of systematic review methodology (PRISMA flow diagram). Two authors searched three electronic databases for literature review, i.e., PubMed, HINARI, and Google Scholar using Mesh-terms, specimen types or molecular diagnostic tests or serological tests in link with COVID-19 or SARS CoV-2, with different combinations, between March 21, 2020 and March 8, 2023. Conclusion: To control the current pandemic of COVID-19 and reduce its burden on healthcare systems around the world, the capacity of diagnostic tests should be improved. Rapid molecular diagnostic tests that can be fast, reliable, cost-effective, available, sensitive, and specific and point of care, must be urgently developed, produced, and widely distributed all over the globe.